The Relationship Between Theological & Sufistic Thought of Sheikh Muhammad Arsyad Al-Banjari: Examining the Book of Hidâyah Al-Râshidîn Al-Mustarsyidîn, the Book of Ushuluddin and Kanz Al-Makrifah - Mujiburrahman, Mujiburrahman; Rusydi, Muhammad; Iqbal, Muhammad (Anterior Jurnal, 2024)
This paper focuses on the relationship between the theological and Sufism thoughts of Shaykh Arshad al-Banjari, especially regarding the concept of twenty attributes and the sentence of tawhid. The study begins with a focus on Hidâyah al-Râshidîn al-Mustarsyidîn. This book, by the descendants of Shaykh Arshad, is attributed to Shaykh Arshad al-Banjari. Through the study of this book, it will be compared with his other works related to the study in the book. Therefore, the comparative method will be used in this study to analyze the relevance of the manuscript of Hidâyah al-Râshidîn al-Mustarsyidîn to the theological and Sufism thoughts of Shaykh Arshad al-Banjari contained in Kitab Ushûluddîn and Kanz al-Maʿrifah, especially related to the concept of the twenty attributes of Allah and the sentence of tawhid. The results show that Hidâyah al-Râshidîn al-Mustarsyidîn is the work of Shaykh al-Jauhari, not the work of Shaykh Arshad al-Banjari, but through this book, it can be assumed that he had a teacher-student relationship with Shaykh al-Jauhari and this book also serves as a link in Shaykh Arshad's theological and Sufism thoughts in Kitab Ushûluddîn and Kanz al-Maʿrifah which emphasize the tawhid of the twenty attributes of Allah and the dhikr of tawhid which is relevant to Imam Sanusi's book Umm al-Barâhin.